Adsorption of 17α-Ethinyl Estradiol and Bisphenol A to Graphene-Based Materials: Effects of Configuration of Adsorbates and the Presence of Cationic Surfactant. (21st April 2021) - Wang, Fang; Sha, Wei; Wang, Xin; Shang, Yuntao; Hou, Lei; Li, Yao
Abstract : Endocrine-disrupting chemicals (EDCs) have attracted much attention in recent years. Graphene-based materials (GMs) have been deemed as excellent adsorbents for the removal of EDCs. The objective of the present study was to understand how the cationic surfactants (CTAB; cetyltrimethylammonium nitrate) affect the adsorption of EDCs (17 α -ethinyl estradiol (EE2) and bisphenol A (BPA)) on graphene oxide (GO), reduced graphene oxides (RGOs), and the few-layered commercial graphene (CG). It was observed that the presence of CTAB showed different effects on the adsorption of EDCs to different GMs. The adsorption of EDCs on GO was enhanced because of the enhanced hydrophobicity of GMs after the adsorption of CTAB and the newly formed hemimicelles by the adsorbed CTAB, which could serve as the partition phase for EDCs. Moreover, the electron donor-acceptor interaction and cation bridging effect of the –NH4 + group of the adsorbed CTAB between EDCs and GMs could also enhance the adsorption of EDCs to GMs. With the increase of the extent of GM reduction, the adsorption enhancement by the presence of CTAB weakened. This could be attributed to the competition and pore blockage effect caused by the adsorbed CTAB. It is worth noting that the enhancement of CTAB on the adsorption of BPA to GMs was more profound than that of EE2. This is likely because the pore blockage effect plays a less important role in the adsorption of BPA due to its smaller molecular diameter and deformable structure.